2021
DOI: 10.7150/ijbs.56657
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2-induced Overexpression of miR-4485 Suppresses Osteogenic Differentiation and Impairs Fracture Healing

Abstract: The angiotensin-converting enzyme 2 (ACE2) receptor has been identified as the cell entry point for SARS-CoV-2. Although ACE2 receptors are present in the bone marrow, the effects of SARS-CoV-2 on the biological activity of bone tissue have not yet been elucidated. In the present study we sought to investigate the impact of SARS-CoV-2 on osteoblastic activity in the context of fracture healing. MicroRNA-4485 (miR-4485), which we found to be upregulated in COVID-19 patients, negatively regulates osteogenic diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 22 publications
0
32
0
1
Order By: Relevance
“…This miRNA has a crucial role to play in tumour biology [ 39 ]. In another recently published study by Mi et al, it was demonstrated that the SARS-CoV-2-induced overexpression of miR-4485 could directly suppress osteogenic differentiation and fracture healing [ 40 ]. This study differed from our study in that the orthopaedic patients selected for the study were either uninfected or SARS-CoV-2 infected once upon a time and were negative for viral RNA at the time of admission to this study.…”
Section: Resultsmentioning
confidence: 99%
“…This miRNA has a crucial role to play in tumour biology [ 39 ]. In another recently published study by Mi et al, it was demonstrated that the SARS-CoV-2-induced overexpression of miR-4485 could directly suppress osteogenic differentiation and fracture healing [ 40 ]. This study differed from our study in that the orthopaedic patients selected for the study were either uninfected or SARS-CoV-2 infected once upon a time and were negative for viral RNA at the time of admission to this study.…”
Section: Resultsmentioning
confidence: 99%
“…For example, miR-155-3p, which is believed to represent a host miRNA passenger stand, was reported to increase upon SARS-CoV and SARS-CoV-2 infection ( 33), but we were unable to detect this miRNA either by sequencing or by Northern blotting (data not shown). Similarly, miR-4485 was described to be upregulated in another study (34), but it did not pass the abundance threshold (> 1 CPM) in our small RNA-seq analysis.…”
Section: Discussionmentioning
confidence: 55%
“…Furthermore, intending to know the effects of SARS-CoV-2 on osteoblastic activity during fracture healing, Mi and coworkers (2021) explored whether COVID-19 infection can predispose patients to osteoporosis. They observed that miR-4485 was upregulated in COVID-19 patients and that this increased miRNA expression has a crucial role in the inhibition of osteogenic differentiation.…”
Section: Studies On Comorbiditiesmentioning
confidence: 99%
“…Additionally, during this investigation, TLR-4 was identified as a potential target gene for miR-4485, and its diminution induced by miR-4485 suppresses osteoblastic differentiation and bone remodeling in SARS-CoV-2 infection. Thus, miR-4485 may provide a promising target for improving fracture healing and anti-osteoporosis therapy in the SARS-CoV-2-infected population ( Mi et al, 2021 ).…”
Section: Studies On Comorbiditiesmentioning
confidence: 99%